Diaphragmatic agenesis in a young adult - S Prabha, Smrithi; Gaude, Gajanan S; Togale, Manoj (Indian Journal of Case Reports, 2025)
Most neonates delivered with diaphragmatic agenesis (DA) do not live more than hours to days. However, very few affected cases survive the childhood period and even their adulthood if treated surgically or conservatively. At laparotomy, there was complete agenesis of the left hemidiaphragm with no diaphragmatic remnants seen and no associated lung hypoplasia. This is an extremely rare condition, and careful assessment is needed to differentiate between diaphragmatic hernia and agenesis of the diaphragm. We have hereby reported a case of neglected left hemi-DA for more than three decades.